Review of A Dutiful Daughter by Thomas Keneally - Evans, Rhondda (LiNQ (Literature in North Queensland), 2016)
A Dutiful Daughter, although not the latest of Keneally’s novels, has not been exhaustively reviewed. Most of the reviews have, to date, assessed it by comparing it with Keneally’s previous works. This review assesses A Dutiful Daughter as a novel whose success or failure depends only on the extent to which all its aspects meet the demands imposed upon them by the distinctive central plot.